Knowledge, Practices and Associated Factors to Sexual and Reproductive Health of Young People of Cotonou, Bénin in 2022 - Lee, Sogbossi D Nancy; Georgia, Damien Barikissou; Badirou, Aguemon (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: The sexual and reproductive health of young people is a public health priority, especially in developing countries such as Benin. The objective of this research is to measure the level of knowledge and practices of young people regarding sexual and reproductive health and the factors associated with it in the city of Cotonou in 2022. Subjects and Method: This is a descriptive cross-sectional study with an analytical focus on a sample of 318 young people aged 15 to 25 years, randomly selected in the community by three-stage cluster sampling. The dependent variables were young people's overall knowledge of sexual and reproductive health with the modalities 'good knowledge' and 'poor knowledge' and young people's SRH practices with the modalities 'good practices' and 'poor practices'. The independent variables were socio-demographic data and individual background and factors. The data were analyzed by logistic regression. Results: In the study population, 51.3% were male with a sex ratio (M/F) of 1.05. The overall level of good knowledge of young people on sexual and reproductive health was assessed at 13.5%. The overall level of good sexual and reproductive health practices of young people was assessed at 72.6%. Good sexual and reproductive health knowledge was more prevalent among young people over the age of 19. The risk of having good SRH knowledge increased eightfold when the type of household in which the young person spent their adolescence was monogamous (OR = 8.03; 95% CI= 2.12 to 30.44; p= 0.017) compared to the single-parent/ isolated household. Conclusion: Promoting sexuality education from early adolescence within communities would be a high-impact solution to improve the quality of sexual and reproductive health of young people and the general population. Keywords: sexual and reproductive health, sexual and reproductive rights, youth, Benin. Correspondence: Sogbossi D. Nancy Lee. Public Health Unit, Faculty of Health Sciences, University of Abomey-Calavi, Cotonou. Email: nleezinsou@gmail.com.